Mongolia’s efforts toward peace and stability in North East Asia - Ochirbat, P (Mongolian Journal of International Affairs, 2011)
DOI: 10.5564/mjia.v0i14.19 Mongolian Journal of International Affairs No.14 2007 pp.27-31